Cirsilineol inhibits RANKL-induced osteoclast activity and ovariectomy-induced bone loss via NF-κb/ERK/p38 signaling pathways - Cong Wang; Rong Zeng; Yong Li; Rongxin He (BMC, 2024)
Abstract Background Postmenopausal osteoporosis is a chronic metabolic bone disease caused by excessive osteoclast formation and function. Targeting osteoclast differentiation and activity can modulate bone resorption and alleviate osteoporosis. Cirsilineol, an active constituent of Vestita Wall, has shown numerous biological activities and has been used to treat many metabolic diseases. However, whether cirsilineol inhibits osteoclast activity and prevents postmenopausal osteoporosis still remain unknown. Materials and methods Primary bone marrow macrophages (BMMs) and RAW264.7 cells were used. Osteoclast activity was measured by TRAP staining, F-actin staining, and bone resorption assay after BMMs were treated with cirsilineol at concentrations of 0, 1, 2.5 and 5 µM. RT-PCR and western blotting were performed to evaluate the expression of osteoclast-related genes. In addition, female C57BL/6 mice underwent OVX surgery and were treated with cirsilineol (20 mg/kg) to demonstrate the effect of cirsilineol on osteoporosis. Results Cirsilineol significantly inhibited receptor activator of nuclear factor-kappa B ligand (RANKL)-induced osteoclast differentiation in a concentration- and time-dependent manner, respectively. Additionally, cirsilineol inhibited F-actin ring formation, thus reducing the activation of bone resorption ability. Cirsilineol suppressed the expression of osteoclast-related genes and proteins via blocking nuclear factor (NF)-κb, ERK, and p38 signaling cascades. More importantly, cirsilineol treatment in mice with osteoporosis alleviated osteoclasts hyperactivation and bone mass loss caused by estrogen depletion. Conclusion In this study, the protective effect of cirsilineol on osteoporosis has been investigated for the first time. In conclusion, our findings prove the inhibitory effect of cirsilineol on osteoclast activity via NF-κb/ERK/p38 signaling pathways and strongapplication of cirsilineol can be proposed as a potential therapeutic strategy.